Pendidikan Perempuan dalam Prespektif Hadis - Imam Nur Ajid; Muhammad Alif (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This writing is intended for equality between women and men so that there are no differences in education. Through the hadith texts of the Prophet and History from pre-prophecy, it cannot be denied that women are second class in life so that many people exclude women compared to men, contrary to what was taught by the Prophet Muhammad SAW who was sent to the face of the earth. This is one way of elevating a woman's status or perfecting her morals to this day, but currently many people in the community think that women's education is not important because women will return to home affairs serving their husbands and educating their children. In contrast to the current life where women can become leaders and can hold positions that men usually hold, such as in government and pubic society. In writing this, the author hopes to change society's mindset to change and improve thinking that does not provide access to women so that women can develop themselves so that they can become useful women in society, especially in their households, in this case not a few women complain. to be able to study and be educated as a man who values ​​education in high regard. This article concludes the importance of women's education that we must change our mindset and provide access to women so that they can develop their potential.